Extraction, evolution, and sensory impact of phenolic compounds during red wine maceration - Casassa, L Federico; Harbertson, James F (Annual review of food science and technology, 2014)
We review the extraction into wine and evolution of major phenolic classes of sensory relevance. We present a historical background to highlight that previously established aspects of phenolic extraction and retention into red wine are still subjects of much research. We argue that management of the maceration length is one of the most determining factors in defining the proportion and chemical fate of phenolic compounds in wine. The extraction of anthocyanins, flavonols, flavan-3-ols, and oligomeric and polymeric proanthocyanidins (PAs) is discussed in the context of their individual extraction patterns but also with regard to their interaction with other wine components. The same approach is followed to present the sensory implications of phenolic and phenolic-derived compounds in wine. Overall, we conclude that the chemical diversity of phenolic compounds in grapes is further enhanced as soon as vacuolar and pulp components are released upon crushing, adding a variety of new sensory dimensions to the already present chemical diversity. Polymeric pigments formed by the covalent reaction of anthocyanin and PAs are good candidates to explain some of the observed sensory changes in the color, taste, and mouthfeel attributes of red wines during maceration and aging.